(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
metaphor is a figure of speech, a rhetorical effect that means one thing by directly mentioning the other. It is possible to identify explicit (or implicit) or hidden similarities between two ideas. Metaphor is often compared to other types of figurative language, such as antithesis, hyperbole, metonymy and comparison